Antenna Beam forming Technology Based Enhanced Metamaterial Superstrates - Bashar B.S.; Rhazali Z.A.; Elwi T.A.; Misran H.; Ismail M.M.; Mahdi M.; Alanssari A.I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Beam forming networks; Beamforming; Metamaterials; Slot antennas; Antenna beams; Antenna system; Beam splitting; Beam-forming; Forming technology; Modern applications; SMPA; Superstrates; Technology-based; Wireless communication technology; Microstrip antennas